The Perils of Premature Judgment: Reading Matthew 21.18–22.14 with the Fig Tree. (March 2023) - Copeland, Rebecca L.
Because fig trees were agriculturally important, residents of Palestine during Jesus's and Matthew's times would be much more familiar with figs than are most academic biblical interpreters. This article engages the cultural, economic, and ecological significance of fig trees in first-century Syrio-Palestine in conversation with the cursing of the fig tree in Mt 21.18–22. This engagement reveals parallels between this passage and the parable of the wedding banquet (Mt 22.1–14), rendering all of Mt 21.12–22:14 as one literary unit centered on the theme of judgment and its timing. Specifically, these two pericopae portray those who render swift judgment as both unreasonable and self-defeating. In contrast, the parables of the two sons (Mt 21.28–31) and the wicked tenants (Mt 21.33–41) show that deferring judgment creates room for repentance, making the literary unit a nuanced explanation of the deferral of divine judgment and an invitation to repentance.